2008
DOI: 10.1074/jbc.m800090200
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Variants of Rhodobacter capsulatus Membrane-anchored Cytochrome cy Are Efficient Photosynthetic Electron Carriers

Abstract: Photosynthetic (Ps) electron transport pathways often contain multiple electron carriers with overlapping functions. Here we focus on two c-type cytochromes (cyt) in facultative phototrophic bacteria of the Rhodobacter genus: the diffusible cyt c 2 and the membrane-anchored cyt c y . In species like R. capsulatus, cyt c y functions in both Ps and respiratory electron transport chains, whereas in other species like R. sphaeroides, it does so only in respiration. The molecular bases of this difference was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…17,18,22 Subtle differences might be due to the presence of detergents, lipids, or other RC subunits in the purified RC or in the native membrane, and the discrepancies are the same range as observed for the soluble variant of membrane-anchored cytochrome c y . 36 These spectroscopic and electrochemical analyses indicate that the recombinant C-cyt c z has the same protein fold and heme group coordination as in the native cyt c z .…”
Section: Discussionmentioning
confidence: 95%
“…17,18,22 Subtle differences might be due to the presence of detergents, lipids, or other RC subunits in the purified RC or in the native membrane, and the discrepancies are the same range as observed for the soluble variant of membrane-anchored cytochrome c y . 36 These spectroscopic and electrochemical analyses indicate that the recombinant C-cyt c z has the same protein fold and heme group coordination as in the native cyt c z .…”
Section: Discussionmentioning
confidence: 95%
“…These fast rates further evidenced that the monitored ETs were mediated by the membranebound cyts c y , and not by their soluble versions (cyt S-c y ), somehow generated by proteolysis. Otherwise, as described in the accompanying work (38), the ET rates would have become much slower. Sharply contrasting the rates, the amplitudes of ET to the RCs were slightly smaller that the unconnected systems even in the presence of a cyt bc 1 -c y complex with a native cyt c y linker, and became progressively smaller with shorter linkers.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the membrane-embedded components can diffuse independently from one another within lipid bilayers, differentiating between static "hardwired" electron transport complexes from those undergoing random collisions (17) is difficult to document in Ps membranes (18). In the accompanying work (38), we have demonstrated by creating soluble variants of cyt c y (cyt S-c y ) that this electron carrier needs not be membrane anchored to support Ps growth of R. capsulatus. In this work, we have exploited the functional cyt bc 1 -c y fusion complex that we constructed earlier by fusing genetically cyt c y to the cyt bc 1 complex (19) to probe the physical proximities of the Ps components to one another in R. capsulatus.…”
mentioning
confidence: 99%
“…fraction A-1) were supplemented with either purified full-length cyt c y , or its soluble variant lacking the TMH (i.e., cyt S-c y ) 32 , to yield the bipartite SC+c y and SC+S-c y samples. Following SEC, the elution fractions showed that only the intact cyt c y , but not the cyt S-c y , remained associated with the SC (Fig.…”
Section: Structure Of Bipartite Sc Supplemented With Cyt C Y the Bimentioning
confidence: 99%
“…construction of strains producing bipartite and tripartite fusion SCs. The Δ(petABC::gm) deletion-insertion allele carried by pYO34 32 was transferred using the gene transfer agent (GTA) into the chromosome of R. capsulatus strain MG1 (ccoP::kan) to yield YO12, providing a mutant background lacking both CIII 2 and the CcoP subunit of CIV. A similar strain, M7G-CBC1 that lacks both CIII 2 and the CcoP subunit but overproduces the CcoN and CcoO subunits of CIV 31 , was also used.…”
Section: Chromosomal Inactivation Of CIII 2 (Cyt Bc 1 ) and Civ (Cbb mentioning
confidence: 99%